Stories of school and childhood: video testimonies for a bottom-up narrative - Macinai, Emiliano; Oliviero, Stefano (Historia y Memoria de la Educación, 2016)
This paper provides an initial report on research, still in progress, aimed at the creation and archiving of video testimonies on the memories of childhood and school among Italians born in the 1940s and 1950s. During this critical period, Italian schools were still based on pedagogical models as well as on teaching practices from previous decades; however, they were also making the first tentative experiments with innovation and launching significant processes of democratisation. Oral testimonies of the experiences of pupils are therefore an undoubtedly valuable source for researchers involved in the complex process of creating the collective memory of school. Archived collections contain a wealth of written and audio-visual documents in which these life stories can be found. Normally, however, at least in the Italian setting, these are ego-documents collected and organised according to other research categories, to which the scholastic experience only serves as background. Memories of the time spent at the school desk were not considered central to the account and often remain part of a much broader context, from which it normally emerges only incidentally. Thus, school years were not the focus of the research. This contribution is therefore an attempt to make an initial resentation of a project involving the creation and collection of numerous video interviews in which memories of school and childhood were the main topic right from the interview planning stage. The ultimate goal of the research is to create a digital video archive of memories about school and education